Taxes as instruments of public policy - Sproule-Jones, Mark, 1941-; Maslove, Allan M. (Research studies of the Fair Taxation Commission of Ontario., 1994)
Taxes are not only a means of raising revenues. Governments also use taxes as instruments to achieve other economic and social policy goals. The role of the user fees to achieve greater efficiency in the production and consumption of publicly provided goods and services is the subject of the first paper in this volume. The following two papers discuss the role of the tax system in human capital investment and the feasibility and impact of a carbon/energy tax, addressing an important concern of environmental policy. The final paper identifies and estimates existing tax expenditures in the Ontario tax system and discusses the implications of these tax measures.